The Use of Social Media as a Means of Digital Literacy: A Literature Study - Yusri Ibrahim; Ian Zulfikar; Kumba Digdowiseiso (CV ODIS, 2023)
This research explores the role of social media as an important tool in increasing digital literacy in modern society. Social media is not only a platform for social interaction, but also a learning resource that facilitates collaboration between teachers, students and parents. The educational role of social media includes sharing educational information, disseminating accurate health information, and active participation in social and political issues. Social media also plays a central role in increasing digital literacy through access to educational materials, digital literacy awareness campaigns, and collaboration between individuals, groups, and organizations. However, digital literacy is faced with challenges such as negative content, false information and cybersecurity risks. The importance of digital literacy education has become abundantly clear in overcoming these challenges. Digital literacy education helps individuals manage information wisely, develop critical thinking skills, and participate in social issues. Social and cultural context also plays an important role in shaping an individual's digital literacy, influencing their values, skills and identity. Joint efforts from the government, society and the education sector are needed to increase digital literacy, ensuring that society can face technological challenges confidently and intelligently in this digital era